Low-Dose Amphotericin B and Murine Dialyzable Spleen Extracts Protect against Systemic Candida Infection in Mice - F. Robledo-Ávila; M. Pérez-Tapia; A. Limón-Flores; L. Pavon; R. Hernández-Pando; I. Wong-Baeza; G. González-González; C. Tovar; S. Estrada-Parra; I. Estrada-García (Clinical and Developmental Immunology, 2013)
Candida albicans causes opportunistic systemic infections with high mortality (30%–50%). Despite significant nephrotoxicity, amphotericin (AmB) is still used for the treatment of this serious fungal infection. Therefore, alternative treatments are urgently needed. Dialyzable leukocyte extracts have been used successfully to treat patients with mucocutaneous candidiasis, but their effectiveness in systemic candidiasis has not been evaluated. In this study, low-dose AmB (0.1 mg/kg) plus 10 pg of murine dialyzable spleen extracts (mDSE) were tested in a systemic candidiasis mouse model. Survival, tissue fungal burden, kidney damage, kidney cytokines, and serum levels of IL-6 and hepcidin were evaluated. Our results showed that the combined treatment of low-dose AmB plus mDSE improved survival and reduced kidney fungal burden and histopathology; these effects correlated with increased kidney concentration of IFN-γ and TGF-β1, decreased levels of TNF-α, IL-6, and IL-10, as well as high levels of systemic IL-6 and hepcidin. Low-dose AmB and mDSE synergized to clear the infectious agent and reduced tissue damage, confirming the efficacy of a low dose of AmB, which might decrease the risk of drug toxicity. Further studies are necessary to explore these findings and its implications in future therapeutic approaches.